Competition and coordination in Swedish botanical publication, 1820–79: Eleven editions of Hartman's Handbook. - Beckman, Jenny (History of Science, 2022)
In 1820, a Handbook of the Flora of Scandinavia by Carl Hartman was published in Stockholm by Zacharias Haeggström. The Handbook was a successful project for both author and publisher: similar enough to textbooks and academic publications to appeal in educational settings, yet ostensibly written for the general public. The Handbook went through eleven editions, becoming the standard reference flora for Swedish botanists – academic as well as others – before being succeeded after 1879 by a range of specialized floras aimed at schoolboys, students, or academic botanists. The trajectory of Hartman's Handbook through the nineteenth century highlights the changing conditions of Swedish botanical publication. It draws attention to authorship as a scientific career tool, and, conversely, the significance of scientific texts in the emergence of commercial publishing in the first half of the nineteenth century.